Diagnosing autism: Australian paediatric research network surveys. (17th January 2016) - Randall, Melinda; Albein‐Urios, Natalia; Brignell, Amanda; Gulenc, Alisha; Hennel, Sabine; Coates, Cathy; Symeonides, Christos; Hiscock, Harriet; Marraffa, Catherine; Silove, Natalie; Bayl, Vivian; Woolfenden, Susan; et al.
Abstract : Aim: Autism spectrum disorder (ASD) is a neurodevelopmental disorder with reported prevalence of more than 1/100. In Australia, paediatricians are often involved in diagnosing ASD and providing long‐term management. However, it is not known how paediatricians diagnose ASD. This study aimed to investigate whether the way Australian paediatricians diagnose ASD is in line with current recommendations. Methods: Members of the Australian Paediatric Research Network were invited to answer questions about their ASD diagnostic practice in a multi‐topic survey and also as part of a study about parents needs around the time of a diagnosis of ASD. Results: The majority of the 124 paediatricians who responded to the multi‐topic survey and most who responded to the parent needs survey reported taking more than one session to make a diagnosis of ASD. Most paediatricians included information from preschool, child care or school when making a diagnosis, and over half included information from speech pathology or psychology colleagues more than 50% of the time. The main reasons for not including assessment information in the diagnostic process were service barriers such as no regular service available or long waiting lists. More than 70% reported ordering audiology and genetic tests more than half of the time. Conclusion: Not all paediatricians are following current recommendations for diagnosing ASD more than 50% of the time. While there are good reasons why current diagnostic approaches may fall short of expected standards, these need to be overcome to ensure diagnostic validity and optimal services for all children and their families.